Comparison of the Stanford ECG Left Atrial Criteria With the International ECG Criteria for Sports Screening. Issue 4 (July 2021) - Hock, Julia; Wheeler, Matthew; Singh, Tamanna; Ha, Le Dung; Hadley, David; Froelicher, Victor
Abstract : Objective: Because the International left atrial enlargement electrocardiographic (ECG) screening criteria (ECG-LAE) for athletes are rarely fulfilled in young athletes, we compared it with evidence-based criteria from a recent clinical outcome study of ECG left atrial abnormality (ECG-LAA). Design: Retrospective analyses. Setting: Routine preparticipation ECG screening in California. Participants: Four thousand four hundred thirty-eight young individuals (18.5 ± 5.4 years, 40% women). Assessment of Risk Factors: The International criteria for ECG-LAE were applied: prolonged P wave duration of ≥120 ms in leads I or II AND negative portion of ≥1 mm in depth in lead V1. This was compared with Stanford criteria for ECG-LAA: prolonged P wave duration of ≥140 ms odds ratio (OR) negative portion in V1 and V2 greater than 1 mm. Main Outcome Measures: Differences in the classification of abnormal ECGs between the 2 criteria applied to the same population of young athletes. Results: Only 33 (0.7%) of our subjects fulfilled the International criteria for ECG-LAE while 110 (2.5%) fulfilled the ECG-LAA criteria. Adding our new ECG-LAA criterion and considering it a major criterion raised the abnormal ECG prevalence and athletes referred for further evaluation from 2.9% to 4.4%. Conclusions: The Stanford evidence-based criterion for ECG-LAA incorporating V2 and replacing "or" for "and" regarding P wave duration increased the yield of abnormal classification for P waves. Future follow-up studies are needed to confirm that this new criterion should be included in future ECG screening consensus documents.